Posterior analytics - Aristotle (Clarendon Aristotle series., 1994)
The Posterior Analytics contains some of Aristotle's most influential thoughts in logic, epistemology, metaphysics, and the philosophy of science. The first book expounds and develops the notions of a demonstrative argument and of a formal, axiomatized science, and investigates in particular the theory of definition. For the second edition of this volume, the translation has been completely rewritten; and the commentary, which is done with the needs of philosophical readers in mind, has been thoroughly revised in the light of the scholarship of the last twenty years.